(untitled) - Spears, Deanne (New York, 2008)
In Tandem: Reading and Writing for College Students is an innovative new text that helps students examine both reading and writing, together in one volume. Throughout the book, students are introduced to reading techniques to ensure thorough comprehension of the material; they are then given thorough instruction in the techniques of writing analytical and argumentative essays. In Tandem recognizes the inseparable nature of reading and writing, and their potential to enhance the learning experience as one, leaving students doubly prepared for the college experience
Keywords: College readers,English language,Report writing,Tiếng Anh; Rhetoric,Problems, exercises, etc.,Tu từ học